Monolingual and Bilingual Infants’ Ability to Use Non-native Tone for Word Learning Deteriorates by the Second Year After Birth - Liu, Liquan; Kager, René (Frontiers in Psychology, 2018)
Previous studies reported a non-native word learning advantage for bilingual infants at around 18 months. We investigated developmental changes in infant interpretation of sounds that aid in object mapping. Dutch monolingual and bilingual (exposed to Dutch and a second non-tone-language) infants’ word learning ability was examined on two novel label-object pairings using syllables differing in Mandarin tones as labels (flat vs. falling). Infants aged 14-15 months, regardless of language backgrounds, were sensitive to violations in the label-objects pairings when lexical tones were switched compared to when they were the same as habituated. Conversely at 17-18 months, neither monolingual nor bilingual infants demonstrated learning. Linking with existing literature, infants’ ability to associate non-native tones with meanings may be related to tonal acoustic properties and/or perceptual assimilation to native prosodic categories. These findings provide new insights into the relation between infant tone perception, learning and interpretative narrowing from a developmental perspective.